2021
DOI: 10.1002/gea.21878
|View full text |Cite
|
Sign up to set email alerts
|

Human–environment interactions at Yangguanzhai, a Middle Neolithic site in the Wei River Valley, northern China: A comprehensive soil‐stratigraphic analysis

Abstract: Yangguanzhai, a Middle Neolithic archaeological site (c. 5500–5000 cal year BP) in the Wei River Valley of China, contains a well‐preserved record of environmental fluctuation, landscape evolution, and human–environment interaction over the Holocene. We examined eight stratigraphic profiles across the site and identified an alternating sequence of sediment and buried soils, indicative of multiple changes in landscape stability. Through this study, we provide a more detailed soil‐stratigraphic framework for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Research in the Weihe and Hanjiang Basins showed that the Mid‐Holocene (7000–4000 B.P.) was the main period of paleo‐soil development and human settlement (Guo et al, 2015; Huang et al, 2011; Kielhofer et al, 2021). The melting ice on the land surface causes the increase of river water volume, the rise of sea water surface, and the relative rise of the erosion base level.…”
Section: Discussionmentioning
confidence: 99%
“…Research in the Weihe and Hanjiang Basins showed that the Mid‐Holocene (7000–4000 B.P.) was the main period of paleo‐soil development and human settlement (Guo et al, 2015; Huang et al, 2011; Kielhofer et al, 2021). The melting ice on the land surface causes the increase of river water volume, the rise of sea water surface, and the relative rise of the erosion base level.…”
Section: Discussionmentioning
confidence: 99%